If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4v = 3v + -8 Reorder the terms: 4v = -8 + 3v Solving 4v = -8 + 3v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-3v' to each side of the equation. 4v + -3v = -8 + 3v + -3v Combine like terms: 4v + -3v = 1v 1v = -8 + 3v + -3v Combine like terms: 3v + -3v = 0 1v = -8 + 0 1v = -8 Divide each side by '1'. v = -8 Simplifying v = -8
| x+3=6x+2 | | -36.838+10m=-2.3(-5.6m+6.5) | | 2y+72=180 | | (3p-2)(p+9)=0 | | h+9.5=-9.7 | | 25x^3+15x^2+2x=0 | | 3x+2(5x+4)=43 | | 7e^5x+8=0.23 | | 8x^2(2x+9)+(2x+9)=0 | | a/10-8=24 | | 5x+2x-3=17 | | 28-2c=6c+4 | | 12x^2-x=16x+40 | | 2p^2+6p+3=0 | | 180=(6x-19)+(3x+32) | | -4r^2+3+r=0 | | 2w+17=21+3w | | 12n+25=-35 | | 6r+4=5r-8 | | 6x-1=4x+27 | | 2y-16=y-6 | | 4r^3=r+3 | | (74x-67y)-(56x+8y)= | | 8x^2+45x+58=0 | | 4y+14=7y+1 | | -4.4s+6.2=8.8s | | 3a^2-6ab+3b^2=0 | | 3-2(3x+1)=3x-(x+3) | | 1.33*n=12 | | 1.33*10=12 | | ln(20)-ln(4)= | | f(x)=x^2+10x+15 |